2010
DOI: 10.1128/jvi.02119-09
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Type 5 E1A and E6 Proteins of Low-Risk Cutaneous Beta-Human Papillomaviruses Suppress Cell Transformation through Interaction with FOXK1/K2 Transcription Factors

Abstract: The adenovirus (Adv) oncoprotein E1A stimulates cell proliferation and inhibits differentiation. These activities are primarily linked to the N-terminal region (exon 1) of E1A, which interacts with multiple cellular protein complexes. The C terminus (exon 2) of E1A antagonizes these processes, mediated in part through interaction with C-terminal binding proteins 1 and 2 (CtBP1/2). To identify additional cellular E1A targets that are involved in the modulation of E1A C-terminus-mediated activities, we undertook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(98 citation statements)
references
References 61 publications
3
95
0
Order By: Relevance
“…Furthermore, these sequences have a similarity to the FoxK1/ K2-interacting domain of adenovirus E1A (Fig. 2E), another protein known to interact with FoxK1 and FoxK2 in a phosphorylation-dependent manner (37). In addition, Thr-493 in human BAP1 is highly conserved among BAP1 homologs (Fig.…”
Section: Identification Of the Foxk1/k2-interacting Region Of Bap1-mentioning
confidence: 90%
“…Furthermore, these sequences have a similarity to the FoxK1/ K2-interacting domain of adenovirus E1A (Fig. 2E), another protein known to interact with FoxK1 and FoxK2 in a phosphorylation-dependent manner (37). In addition, Thr-493 in human BAP1 is highly conserved among BAP1 homologs (Fig.…”
Section: Identification Of the Foxk1/k2-interacting Region Of Bap1-mentioning
confidence: 90%
“…A number of previous immunoprecipitation studies using the well-defined hAd5 E1A mutant dl1102 (18) have identified the interaction of TRRAP (8, 10) and p400 (11) with the E1A domain encompassing residues 26 to 35. During our unbiased proteomic analyses of cellular proteins associated with L-E1A and S-E1A (20,22), we detected associations of several proteins (in addition to TRRAP, p400, and GCN5) that we reasoned might be constituents of the TRRAP/p400 and TRRAP-GCN5 complexes. These proteins included Tip49, Tip50, BAF53, c-MYC, MYCBP, and ENY2.…”
Section: Defining the Transforming Activity Of E1a N-terminal Domainsmentioning
confidence: 99%
“…The E1A-associated cellular protein complexes were prepared from KB cells infected with hAd5 mutants that express epitope-tagged (Flag and HA) S-E1A (FH-12S) or L-E1A (FH-13S). The protein complexes were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…Knockdown TAP and MS. To isolate cellular protein complexes associated with S-E1A and L-E1A, a suspension culture of KB cells was mock infected or infected with HF-12S or HF-13S. Tandem affinity purification (TAP) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) analyses were carried out as previously described (25).…”
Section: Methodsmentioning
confidence: 99%